Clinical study on electroacupuncture for obese patients with binge eating disorder: A retrospective study. Issue 49 (4th December 2020) - Cheng, Changcheng; Liu, Xuzhen; Zhu, Shuibing; Dong, Can; Liu, Lei; Lin, Wanqi; Deng, Han; Xu, Yuqi; Ou, Zengjian; Lyu, Wanyong; Zhang, Cairong
Abstract : Abstract: Binge eating disorder (BED) is a common dietary disorder among obese people. Obesity and eating disorders are related to mental health and physical health. At present, there is no definite and effective method for treatment in clinic. The curative effect of electroacupuncture on obesity is definite. Although there is no conclusive evidence to support its long-term benefits, electroacupuncture has been increasingly used in clinic. This retrospective study determined the prognosis and outcome of electro-acupuncture on obese patients with BED. One hundred forty-three patients with BED and obesity were found from 658 people who participated in the scientific experiment of obesity treatment in Nanjing Hospital of Traditional Chinese Medicine and Nanjing Brain Hospital from March 2015 to June 2018, and 84 patients (aged 18–40 years old) with valid data and uninterrupted treatment were found to be eligible for this retrospective study. According to the intervention methods, the patients were divided into electro-acupuncture combined with cognitive group (n = 32), cognitive therapy group (n = 28), and control group (n = 24). In this study, the 5th edition of Diagnosis and Statistics Manual of Mental Diseases, fasting blood glucose, fasting insulin, total cholesterol (TC), triglyceride, high-density lipoprotein, low-density lipoprotein, body fat rate, muscle mass, visceral index grade, nutrient intake (energy, protein, fat, carbohydrate), body weight, and weight changes before and after treatment were observed. Compared with the cognitive therapy group, negative emotion score, TC, triglyceride, high-density lipoprotein, waist circumference, BW, BMI, body fat percentage of the electroacupuncture combined with cognitive group were lower, while positive emotional scores were higher, and there were significant differences in negative emotional scores, TC, waist circumference and BMI ( P < .05). The dietary energy and three major nutrients in the electroacupuncture combined with cognitive group were lower than those in the cognitive group and the blank group ( P < .05). The current results suggest that electroacupuncture combined with cognitive therapy is more effective than cognitive therapy alone in treating obese patients with BED. Future prospective studies are necessary to further study the mechanism of electroacupuncture on the obese with BED.